Eco fashion is an important step in the conservation of nature - Abdukodirova Nargiza Abdurahimovna (Zien Journals, 2022)
The article discusses the concept of eco-fashion in the context of efforts to protect the environment in line with the socio-economic processes taking place in the world community in the 21st century
Keywords: Eco-fashion; current trend; fashion management; sustainable